Kramers-Kronig Receivers for 100-km Datacenter Interconnects - Chen, Xi; Antonelli, Cristian; Chandrasekhar, Sethumadhavan; Raybon, Gregory; Mecozzi, Antonio; Shtaif, Mark; Winzer, Peter (Journal of lightwave technology, 2018)
In this paper, we review in detail experimental demonstrations of Kramers-Kronig (KK) based direct detection systems with high per-carrier interface rates, high spectral efficiencies, and ∼100-km reach. Two realizations of KK-based receivers are summarized, including single-polarization and dual-polarization versions. Critical aspects of the KK receiver such as the carrier-to-signal power ratio and receiver bandwidth limitations are discussed. We show 220-Gb/s single-diode detection and 4 × 240-Gb/s dual polarization (dual-diode) detection in a WDM system at 5.3 bits/s/Hz spectral efficiency.